P141 A service evaluation for and on behalf of the European Clinical Collaborative Group (ECCG) - The management of Gonorrhoea across Europe. (30th June 2016) - Aadan, Hibak; Mawdsley, James; Eatwell, Harriet; Clarke, Emily; Gomberg, Mikhail; Kovalyk, Vladimir; Moi, Harold; Poder, Airi; Ross, Jonathan; Unemo, Magnus; White, John; Patel, Rajul
Abstract : Background/introduction: Gonorrhoea (GC) cases appear to be rising as well as increasing problems with resistance to many antibiotic groups. With open boundaries and free movement of populations and doctors, a consistent standard of care is important across Europe. Regular evaluation is crucial in controlling the emergent spread of resistant GC. Aim(s)/objectives: To evaluate current clinical practice amongst sexual health physicians across Europe against the current European guidelines. Also, key areas of controversy will be explored with to help inform further guideline development. Methods: The ECCG is a network of 120 sexual health specialists across 38 countries, who conduct questionnaire-based research across the European region. An expert panel consisting of six ECCG members was established then interviewed to help identify areas of controversy. Subsequently, a clinical scenario based questionnaire was developed then disseminated to all ECCG members. Results: Provisional results demonstrate variation in clinical practice across Europe. This is discernable from the choice of treatment for a patient with a history of anaphylaxis to penicillin and treatment for confirmed pharyngeal infection. In addition, data showed a lack of consensus to guidelines regarding choices of look back period for sexual contacts. Discussion/conclusion: Management of GC varies across Europe and is not always in line with current European guidelines. Although there are minor variations between guidelines, there are vast discrepancies amongst European clinicians regarding clinical practice. There is a need for on-going Europe wide education to ensure that patients are receiving safe evidence based care.